2020
DOI: 10.25122/jml-2020-0117
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Significance of Matrix Metalloproteinase-2 and Matrix Metalloproteinas-9 in Endometriosis

Abstract: Endometriosis is a chronic benign hormone-dependent condition when the endometrial tissue, identical with the endometrium by its morphological and functional properties, grows outside the borders of the uterine mucous membrane. Recent studies have pointed to the possible role of matrix metalloproteinases (MMPs) in the pathogenesis of endometriosis. We suggested a hypothesis that increased expression of MMPs activity in eutopic and ectopic endometrium of patients with endometriosis might correlate with the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…In agreement, it is demonstrated that the cultured CD146 + human endometrial cells in the collagen/matrigel scaffold in the presence of MSMCs resulted in the expression of ZO-1, COL4A1, and LAMA2 genes at the mRNA level as well as the formation of glandular-like structures at the morphological and ultrastructural levels [19]. The osteopontin (SPP1) and matrixmetaloproteinase-2 (MMP2) proteins are secreted by the endometrial epithelial and stromal cells [27][28][29][30][31]. Osteopontin plays a role in embryo implantation, placenta formation, cell-to-cell adhesion, and proliferation and migration of endometrial cells [27][28][29] and the MMP proteases have an essential function in endometrial tissue remodeling during the menstrual cycle [30][31].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In agreement, it is demonstrated that the cultured CD146 + human endometrial cells in the collagen/matrigel scaffold in the presence of MSMCs resulted in the expression of ZO-1, COL4A1, and LAMA2 genes at the mRNA level as well as the formation of glandular-like structures at the morphological and ultrastructural levels [19]. The osteopontin (SPP1) and matrixmetaloproteinase-2 (MMP2) proteins are secreted by the endometrial epithelial and stromal cells [27][28][29][30][31]. Osteopontin plays a role in embryo implantation, placenta formation, cell-to-cell adhesion, and proliferation and migration of endometrial cells [27][28][29] and the MMP proteases have an essential function in endometrial tissue remodeling during the menstrual cycle [30][31].…”
Section: Discussionmentioning
confidence: 84%
“…The osteopontin (SPP1) and matrixmetaloproteinase-2 (MMP2) proteins are secreted by the endometrial epithelial and stromal cells [27][28][29][30][31]. Osteopontin plays a role in embryo implantation, placenta formation, cell-to-cell adhesion, and proliferation and migration of endometrial cells [27][28][29] and the MMP proteases have an essential function in endometrial tissue remodeling during the menstrual cycle [30][31]. Myometrial cells secrete some factors, ECM components, and substances that play an inductive role in the epithelialization of human endometrial tissue as well as cell proliferation, differentiation, migration, attachment, polarity, and apoptosis [32].…”
Section: Discussionmentioning
confidence: 99%
“…These arteries provide oxygen and nutrition to endometriosis lesions, hence supporting their growth and survival [ 52 , 53 ]. Tissue remodeling is promoted by MMP-2 and MMP-9, which play a role in the generation of adhesions, the fibrous tissue that can cause tissues to adhere together in endometriosis [ 54 ]. Also, other factors can influence the levels of MMP-2, MMP-9, and TGF-β1 in endometriosis, including estrogen and progesterone, which are the primary sex hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs) are a family of endopeptidases that play specific roles in ECM degradation and turnover (Almeida et al 2022 ). For example, in patients with endometriosis, the expression of MMP-2 and MMP-9 in the endometrium is increased, which in turn promotes the rupture of peritoneal ECM and the establishment of peritoneal endometriosis foci through the increase in MMP activity in the endometrium (Barbe et al 2020 ). Similarly, Wang et al (Wang et al 2019 ) detected high levels of HE4 in the serum of patients with pulmonary fibrosis (CF).…”
Section: Discussionmentioning
confidence: 99%